Social trust in the midst of pandemic crisis: Implications from COVID-19 of South Korea - Kye, Bongoh; Hwang, Sun-Jae (Research in social stratification and mobility, 2020)
•COVID-19 pandemic crisis is dramatically changing all aspects of human interactions, including social trust.•With unique panel data collected amid the COVID-19 in South Korea, we examined changes in social trust toward various social institutions.•Trust in society, people, and the government improved, whereas trust in judicature, the press, and religious organizations decreased.•Improvement in trust was associated with proactive responses to the pandemic crisis, and failure to do so resulted in the deteriorating trust.•This study contributes to the understanding of relations between risk management and social trust with the COVID-19 situation in South Korea. This study aims to exploit the situations imposed by the COVID-19 pandemic crisis in South Korea to identify the causal effect of a pandemic crisis and institutional responses on social trust. With unique panel data collected in the course of the COVID-19 in South Korea and the use of individual fixed-effects models, we examined how social trust in various social institutions changed and identified a causal effect of crisis management on social trust. According to the results, trust in South Korean society, people, and the central and local governments improved substantially, whereas trust in judicature, the press, and religious organizations sharply decreased. Improvement in trust in the central and local governments was associated with proactive responses to the pandemic crisis, and failure to take appropriate actions was responsible for the deteriorating trust in religious organizations. These findings illustrate the importance of risk management in trust formation and imply that South Korea may be transforming from a low-trust to a high-trust society.